PreciSSIon: a collaborative initiative to reduce surgical site infections after elective colorectal surgery. (December 2022) - Clayphan, B.; Dixon, L.; Biggs, S.; Jordan, L.; Pullyblank, A.; ,; Holden, K.; Walker, D.; Pitts, K.; Bertman, K.; Glancy, D.; Andrews, S.; et al.
Summary: Background: Surgical site infections (SSIs) are common after colorectal surgery, but most hospitals do not know their SSI rates. Approximately half of SSIs occur after discharge, and postdischarge surveillance is needed for accurate measurement. Perioperative care bundles are known to reduce SSI rates. PreciSSion is a collaboration between seven hospitals in the West of England. Aims: To establish reliable SSI measurement after elective colorectal surgery using 30-day patient-reported outcome measures, and to implement an evidence-based four-point care bundle that had already demonstrated a reduction in the SSI rate in a local hospital. The bundle included: 2% chlorhexidine skin preparation, a second dose of antibiotic after 4 h, use of a dual-ring wound protector, and use of antibacterial sutures for abdominal wall closure. Methods: The 30-day patient-reported SSI rate was determined using the Public Health England questionnaire, and response rates were recorded. The baseline SSI rate was measured from November 2019 to May 2020, and continued after implementation of the care bundle until March 2021. Bundle compliance was also measured. Findings: The average questionnaire response rate was 81%, and average compliance was 92%, 96%, 79% and 85% for each element of the bundle. The baseline SSI rate was 8–30%. Six of seven hospitals reduced their SSI rate, and the regional average SSI rate almost halved from 18% (1447 patients) to 9.5% (1247 patients). Conclusion: A care bundle developed in a single hospital can be adopted in other hospitals, and a 50% reduction in SSI rate after elective colorectal surgery can be replicated in other hospitals within 18 months.